Identification of N7-methylguanosine-related IncRNA signature as a potential predictive biomarker for colon adenocarcinoma - Ma, Xiaomei; Yang, Baoshun; Yang, Yuan; Wu, Guozhi; Ma, Xiaoli; Yu, Xiao; Li, Yingwen; Wang, Yuping; Guo, Qinghong (Frontiers in Genetics, 2022)
N7-methylguanosine (m7G) is an RNA modification serving as a key part for colon cancer development. Thus, a comprehensive analysis was executed to explore prognostic roles and associations with immune status of the m7G-related lncRNA (m7G-RNAs) in colon adenocarcinoma (COAD). Identification of m7G-RNAs was achieved via Pearson’s correlation analysis of lncRNAs in TCGA-COAD dataset and m7G regulators. A prognostic signature was developed via LASSO analyses. ESTIMATE, CIBERSORT and ssGSEA algorithms were utilized to assess immune infiltration between different risk groups. Survival analysis suggested the high-risk group possess poor outcomes compared with the low-risk group. According to the ROC curves, the m7G-RNAs signature exhibited a reliable capability of prediction (AUCs at 1, 3 and 5 years were 0.770, 0.766 and 0.849, respectively). Multivariate hazard analysis proved the signature was an independent predictive indicator for OS. Moreover, the risk score was related to infiltration levels of naïve B cells, CD4+ memory T cells and resting NK cells. The result revealed the prognostic value of m7G modification in COAD and provide novel perspective on personalized immunotherapy strategies.